The Community of Ukrainians in Romania. The Case of Târnova Commune (Arad county): Identity Aspects, Political Representation, Language and Religion. Field Research July 22-24, 2011 - Maria Hadiji (Dialogica: Revistă de Studii Culturale și Literatură)
Ukrainians represent a large Slavic group in Romania, being the third largest ethnic minority group (according to the data provided by the censuses of 1992, 2002, 2011 and 2022) being settled in Maramureş, Bucovina, Banat and Dobrogea. The Ukrainian community in Banat, concentrated in a few villages in the area of Lugoj, Caransebes and Arad, was established especially between the years 1908–1918. Unlike other minority nationalities whose seniority on a foreign territory has barely reached a century, the Ukrainians have not managed to establish themselves in well-knit communities. Following a field study carried out by us between July 22-24, 2011, in Târnova commune (Arad county), representative in terms of the share of ethnic Ukrainians at the county level, the data obtained are included in this general picture, the community hence not being homogenous either in terms of language or in terms of religious affiliation or identity, and the last census carried out in 2022, records a drastic decrease in the number of ethnic Ukrainians (481), thus illustrating a not gratifying fact, in the given context.